2017
DOI: 10.3390/s17020287
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis by Volatile Organic Compounds in Exhaled Breath from Lung Cancer Patients Using Support Vector Machine Algorithm

Abstract: Abstract:Monitoring exhaled breath is a very attractive, noninvasive screening technique for early diagnosis of diseases, especially lung cancer. However, the technique provides insufficient accuracy because the exhaled air has many crucial volatile organic compounds (VOCs) at very low concentrations (ppb level). We analyzed the breath exhaled by lung cancer patients and healthy subjects (controls) using gas chromatography/mass spectrometry (GC/MS), and performed a subsequent statistical analysis to diagnose l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 45 publications
0
54
0
1
Order By: Relevance
“…Breath gas mainly contains nitrogen and carbon dioxide produced by respiration. It consists of more than 100 gas species with different concentrations, which may provide useful information for early diagnosis of disease [ 69 ]. However, breath test has some drawbacks, such as insufficient accuracy because exhaled air has many crucial volatile organic compounds (VOCs) at very low concentrations and there is no clear protocol for breath sampling [ 70 ].…”
Section: Clinical Lung Screening Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Breath gas mainly contains nitrogen and carbon dioxide produced by respiration. It consists of more than 100 gas species with different concentrations, which may provide useful information for early diagnosis of disease [ 69 ]. However, breath test has some drawbacks, such as insufficient accuracy because exhaled air has many crucial volatile organic compounds (VOCs) at very low concentrations and there is no clear protocol for breath sampling [ 70 ].…”
Section: Clinical Lung Screening Modalitiesmentioning
confidence: 99%
“…They also performed a subsequent statistical analysis to detect lung cancer by combining various VOCs. Their research findings indicated that the five-element VOC pattern of CHN, methanol, CH3CN, isoprene, and 1-propanol is sufficient for 89% screening accuracy [ 69 ].…”
Section: Clinical Lung Screening Modalitiesmentioning
confidence: 99%
“…(26)(27)(28)(29)(30)(31) In this case study, good separation depends on the suitable choice of feature functions after DWT decomposition. The EMG raw data are obtained from the specified experiments for eight different persons.…”
Section: Classification Of Emg Signals Using Svmmentioning
confidence: 99%
“…SVM is a supervised model for linear regression analysis on nonlinear data sets. SVM-based classification of samples in the analysis of metabolite profiles from GC-MS and LC-MS has been reported, 18,19 but efficient SVM models optimized for TOF-SIMS data analysis using clinical samples have not yet been defined.…”
Section: Introductionmentioning
confidence: 99%